Renal cystadenocarcinoma-nodular dermatofibrosis syndrome in a German Shepherd canine - Case report (Research, Society and Development, 2022)
The objective of this study is to describe the clinical, ultrasound, serum and anatomopathological aspects of renal cystadenocarcinoma-nodular dermatofibrosis (SCRDN) in an eight-year-old female German Shepherd dog treated at the Hospital Veterinário of Universidade de Cruz Alta (HV/ UNICRUZ). The animal had a history of abdominal pain and vomiting. Clinical examination revealed a nodule in the left hind limb. The animal was submitted to complementary examinations of ultrasound, hematology, biochemical profile and fine needle aspiration cytology (FNAC) of the cutaneous nodule. Ultrasonography detected enlargement of the kidneys and the presence of anechoic vacuoles distributed throughout the organ. In the biochemical profile there was an increase in the levels of urea and creatinine. Due to the evolution of the condition, the patient was euthanized and referred to the Laboratório de Patologia Veterinária at UNICRUZ (LPV/UNICRUZ). During necropsy, enlarged kidneys were observed, with a bossed surface and areas of omentum adherence. When cut, they were cystic, multiloculated and filled with material either liquid and red or hemorrhagic, with a necrotic appearance. Fragments of all organs were collected, fixed in 10% buffered formalin. After 48 hours, the samples were routinely cleaved and processed to make histological slides. In the microscopic evaluation of the kidney, areas of cystification were observed, covered by neoplastic cuboidal epithelium and, occasionally, solid areas of these tumor cells in the middle of the renal parenchyma. We also observed areas of interstitial fibrosis, tubular degeneration and necrosis and thickening of the renal capsule, with areas of subcapsular hemorrhage. The diagnosis of renal cystadenocarcinoma was based on the history, imaging and biochemical tests, confirmed by macroscopic and histopathological findings.